1982
DOI: 10.1093/nar/10.17.5255
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the adducts formed between [Pt(dien)C1]C1 and DNAin vitro

Abstract: The products of the reaction between [Pt(dien)Cl]Cl and salmon sperm DNA have been purified and their structures determined. [Pt(dien)Cl]Cl binds at the N7 position of guanine for levels of fixation below 0.1 platinum per DNA base. Above this level of binding, [Pt(dien)Cl]Cl also reacts at the N7 position of adenine. 1,7-[Pt(dien)]2Ade was observed when more than 0.3 platinum per base were bound to the DNA. Platination at the N7 position of guanosine, unlike alkylation, stabilized the glycosyl linkage and did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…The glycosyl linkage of guanine residues modified at the N7 position by the monofunctional platinum derivative dienPt is more resistant to acid hydrolysis than that of the unmodified residues (Johnson, 1982;Johnson et al, 1982). We have studied the relative stability of glycosyl linkages of guanine residues modified by cisPt.…”
Section: Nature Of the Adductsmentioning
confidence: 99%
“…The glycosyl linkage of guanine residues modified at the N7 position by the monofunctional platinum derivative dienPt is more resistant to acid hydrolysis than that of the unmodified residues (Johnson, 1982;Johnson et al, 1982). We have studied the relative stability of glycosyl linkages of guanine residues modified by cisPt.…”
Section: Nature Of the Adductsmentioning
confidence: 99%
“…In support of this idea, Brouwer et al (1981) have found that cisplatin strongly favors G.C to T.A transversions among 650 nonsense mutations produced in the lacI gene of Escherichia coli, supporting the idea that what is occurring is depurination followed by bypass repair. Pt(dien)CIappears to strengthen the glycosyl bond when it complexes with the N7 position of guanine (Johnson, 1982;Johnson et al, 1982). However, as these authors themselves point out, 'The enhanced biological activities of cis-PDD compared with trans-PDD and [Pt(dien)Cl]Cl are a consequence of different platinum-DNA adducts formed by these compounds in vivo'.…”
Section: Introductionmentioning
confidence: 99%
“…The binding to the latter residues is, however, noticeably slower than to other DNA base residues, and in general the DNA binding of Com2 is slower than that of Com1. Thus, these results suggest that Com1 and Com2 bind to different base residues in DNA and have different base sequence preferences than their simpler analogs cisplatin or [Pt-Cl(dien)]Cl, which both bind preferentially to guanine residues, and cisplatin to a less extent to adenine residues (Johnson et al, 1982, Fichtinger-Schepman et al, 1985Eastman, 1987).…”
Section: Resultsmentioning
confidence: 93%